HUBUNGAN TINGKAT SPIRITUAL DENGAN KUALITAS HIDUP LANSIA DI KABUPATEN GOWA - Aidah Fitriani; Nur Sayyidah; Rasdiyanah Rasdiayanah; Eny Sutria; Titi Mildawati (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
Quality of life aspects include physical health, psychological well-being, independence, social relationships, relationships with the environment, and spiritual well-being. A good quality of life is characterized by optimal functional condition in the elderly when spiritual aspects are met. This is expected to improve the quality of life of the elderly, enabling them to enjoy their old age with meaning and happiness. The purpose of this study was to determine the relationship between the spiritual level of the elderly and the quality of life of the elderly in the Samata Community Health Center (Puskesmas) work area. This study used a quantitative and descriptive analytical design with a cross-sectional study approach using the SWBS and WHOQOL-OLD questionnaires, and analyzed using the Chi-Square statistical test. The results of the univariate study showed that the majority of elderly people were in the high spiritual level category and had a high quality of life (64.6%). Meanwhile, the bivariate test showed a significant relationship between spiritual level and quality of life in the elderly with a p-value of 0.011. The conclusion of this study is that the higher the spiritual level of the elderly, the higher the quality of life.